Workshop Penggunaan Sistem Informasi Pembayaran SHP Versi 1.0 Koperasi Unit Desa (KUD) Hemat - Imam Saputra; Kurnia Ulfa; Annisa Fadillah Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Koperasi Unit Desa Hemat in collaboration with PT. Sago Nauli to process the results of oil palm plantations owned by local residents with a plasma oil palm plantation system, namely oil palm plantations owned by residents whose maintenance and development are carried out by PT. Sago Nauli through the mediation of Koperasi Unit Desa Hemat. manages 684 plots of land or the equivalent of 1368 hectares of oil palm land, and has 762 active members. The remaining Production Results (SHP) are always distributed to members of the oil palm land owners regularly in the middle of the month. Each member has a book that is used as evidence as well as a book to write down the distribution of SHP data. The writing in the book still uses a manual method so it is prone to errors or data falsification. Therefore a computer-based system is needed to minimize errors or falsification of data. Another obstacle faced is the unstable supply of electricity and frequent blackouts, making the use of electrically sourced electronic goods vulnerable to damage. Therefore, a reliable information system is needed that can be used to overcome errors that occur and can withstand unstable and frequent power outages. The implementation of this training program lasted for 2 days, due to the limited time of the participants in this community service activity. the implementation of activities is carried out at the Savings Village Unit Office. The training program is carried out by explaining as well as simulating the use of the SHP payment information system. By knowing and understanding the steps for using the Remaining Production Payment Information System (SHP), the management of the Cahaya Village Cooperative Unit no longer needs to record transactions manually to book members, printing member books can be done through the system that has been built.